2020
DOI: 10.1002/jcp.29675
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA 2193 regulates meiosis through global epigenetic modification and cytoskeleton organization in pig oocytes

Abstract: Long noncoding RNAs (lncRNAs) regulate a variety of physiological and pathological processes. However, the biological function of lncRNAs in mammalian germ cells remains largely unexplored. Here we identified one novel lncRNA (lncRNA2193) from single‐cell RNA sequencing performed on porcine oocytes and investigated its function in oocyte meiosis. During in vitro maturation (IVM), from germinal vesicle (GV, 0 hr), GV breakdown (GVBD, 24 hr), to metaphase II stage (MII, 44 hr), the transcriptional abundance of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Specifically, we identified 148 DE lncRNAs and 811 DE mRNAs in ovaries between the groups of high and low egg production performance. In the last few years, numerous studies had found that lncRNAs played important roles in the oogenesis in ovaries of different species, including pigs, cattle, mice and ducks (Nakagawa et al, 2014;Ren et al, 2017;Yang et al, 2020). The present study is the first to report the transcriptome profiling of lncRNAs and mRNA in the ovaries of pigeons.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Specifically, we identified 148 DE lncRNAs and 811 DE mRNAs in ovaries between the groups of high and low egg production performance. In the last few years, numerous studies had found that lncRNAs played important roles in the oogenesis in ovaries of different species, including pigs, cattle, mice and ducks (Nakagawa et al, 2014;Ren et al, 2017;Yang et al, 2020). The present study is the first to report the transcriptome profiling of lncRNAs and mRNA in the ovaries of pigeons.…”
Section: Discussionmentioning
confidence: 56%
“…LncRNAs have also been found to be key regulators in a wide range of biological processes, including reproduction, but most of the mechanisms of lncRNA related regulation in biological processes remain unclear (Taylor et al, 2015). In the terms of animal genetics, the effects of lncRNAs on economically important phenotypic traits had been studied in the last decade (Zhang et al, 2019;Yang et al, 2020), particularly for the possible application in poultry breeding (Fulton, 2012). However, lncRNAs, as the crucial regulation factors in many biological processes, have not been systematically researched in the ovaries of domestic pigeons related to egg production.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a role for meiosis progression has been suggested for Tsx, an X-linked lncRNA differentially expressed in PS, as knockout mice show increased PS apoptosis (Anguera et al, 2011). On the other hand, 2193 lncRNA has been identified by means of scRNAseq, and shown to play an important role in porcine oocyte maturation through epigenetic modification (Yang et al, 2020).…”
Section: Meiotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 96%
“…In humans with testicular cancer, SCs showed aberrant MAPK, AMPK and TGF-β/Smad signaling pathways [ 51 ]. LncRNAs was longer than 200 nt, which could not be translated into any protein, but could regulate the expression of target genes and function in multiple biological processes [ 56 ]. Recently, lncWNT3-IT has been shown to regulate WNT3 expression and affect proliferation of goat SCs, confirming the vital function of lncRNAs in SCs [ 57 ].…”
Section: Discussionmentioning
confidence: 99%